2018
DOI: 10.17227/rce.num75-8100
|View full text |Cite
|
Sign up to set email alerts
|

The Journey towards Inclusion: Exploring the Response of Teachers to the Challenge of Diversity in Schools

Abstract: The general objective of the research presented in this article was to explore the attention to the diversity of students in kindergartens, and primary and high schools in the Region of Murcia (southeast of Spain). This study adopted a methodology of a quantitative nature. The instrument used to collect the data was the Themis Inclusion Tool (Azorín and Ainscow, 2018), which is a Likert scale aimed at teachers formed by three dimensions: contexts, resources and processes. Themis was administered to 545 teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
(29 reference statements)
0
2
0
2
Order By: Relevance
“…In this case, both sexes agree. If we look for significant differences in the responses according to the location of the center, there are only differences between teachers in urban and rural centers when talking about the positive effect of integration on emotional development and that it favors the preparation of students to live in society, two statements in which the responses are conditioned by the location of the educational center where classes are taught [39].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, both sexes agree. If we look for significant differences in the responses according to the location of the center, there are only differences between teachers in urban and rural centers when talking about the positive effect of integration on emotional development and that it favors the preparation of students to live in society, two statements in which the responses are conditioned by the location of the educational center where classes are taught [39].…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating this result, a scoping review by Finkelstein et al [5] highlighted collaboration and teamwork, instructional practices, organizational practices, social/emotional/behavioural practices, and determinations of progress as domains related to inclusive teaching practices. Other research has found that inclusive practices include the celebration of diversity, teaching planning, the taking into account of all students, education process, a varied methodology, formation of flexible and heterogeneous groups, the organization of times and spaces, support, and evaluation and transit between education stages [16,17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…El cuarto ámbito temático agrupa publicaciones que abordan principalmente disposiciones hacia la inclusión de la diversidad, vale decir, tendencias para actuar de una particular manera bajo circunstancias específicas. En este conglomerado encontramos investigaciones que abordan las subjetividades sociales, percepciones y reflexiones docentes, concepciones docentes, actitudes sociales, entre otras (Santos & Martínez, 2016;Vasconcellos et al, 2016;Cunha & Gomes, 2017;Versoza-Carvalhal et al, 2017;Azorín-Abellán, 2018;Maturana et al, 2019;Cano-Muñoz & Gómez-Nuñez, 2020). Este conglomerado apela a que las disposiciones profesionales hacia la diversidad se relacionan de manera estrecha con las valoraciones y concepciones que tenga la escuela hacia la inclusión.…”
Section: ¿Cuáles Son Los Principales áMbitos De Acción De Los Estudio...unclassified